Measuring magnetocaloric effect in a phase separated system. (23rd November 2018) - Goijman, D; Leyva, A G; Quintero, M
Abstract: The magnetocaloric effect (MCE) in a magnetic system can be characterized by the estimation of the entropy change produced when a magnetic field is applied. The discrepancies between the results obtained with different methods have encouraged the scientific community to attempt to better understand the procedures associated with this calculation. Within this context, we present a study about how the presence of an inhomogeneous state influences the determination of the entropy change. To do that we chose a prototypical system used to study the phase separation phenomena in manganites. We compared results obtained using different methods, and we propose an approach to correlate the results obtained following different procedures.